Perlindungan Konsumen terhadap Praktik Jual Beli Barang Kadaluwarsa yang Tidak Dapat Dikembalikan - Sayidah Nisrul Halimatus Sakdiyah (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
This article is the result of a qualitative research to answer questions about how the practice of buying and selling expired goods that cannot be returned at Hidayah store and how Islamic law and Law no. 8 of 1999 concerning consumer protection against the sale and purchase of expired goods that cannot be returned at the Hidayah store in Surabaya. From the results of this study, it can be concluded that: first, in practice, expired goods which are the object of buying and selling at the Hidayah store in Surabaya may not be returned when consumers directly choose their own goods at the store, while they can be returned if the customer places an order by telephone; second, the practice of buying and selling expired goods that cannot be returned is not allowed according to Islamic law, because it is not in accordance with the sale and purchase contract in which there is a khiya>r, namely disgrace khiya>r, where when the goods are defective (expired), then may be returned. In addition, in article 8 paragraph 4 of Law no. 8 of 1999 concerning consumer protection also emphasized the prohibition of business actors from trading expired goods and being obliged to withdraw them from circulation. Consumers should be more thorough and careful in checking the goods to be purchased by checking the expiration date of each food product. Meanwhile, shop owners should sell goods that do not expire so as not to harm consumers.